SLC6A14, a Pivotal Actor on Cancer Stage: When Function Meets Structure. (October 2019) - Palazzolo, Luca; Paravicini, Chiara; Laurenzi, Tommaso; Adobati, Sara; Saporiti, Simona; Guerrini, Uliano; Gianazza, Elisabetta; Indiveri, Cesare; Anderson, Catriona M. H.; Thwaites, David T.; Eberini, Ivano
SLC6A14 (ATB 0, + ) is a sodium- and chloride-dependent neutral and dibasic amino acid transporter that regulates the distribution of amino acids across cell membranes. The transporter is overexpressed in many human cancers characterized by an increased demand for amino acids; as such, it was recently acknowledged as a novel target for cancer therapy. The knowledge on the molecular mechanism of SLC6A14 transport is still limited, but some elegant studies on related transporters report the involvement of the 12 transmembrane α-helices in the transport mechanism, and describe structural rearrangements mediated by electrostatic interactions with some pivotal gating residues. In the present work, we constructed a SLC6A14 model in outward-facing conformation via homology modeling and used molecular dynamics simulations to predict amino acid residues critical for substrate recognition and translocation. We docked the proteinogenic amino acids and other known substrates in the SLC6A14 binding site to study both gating regions and the exposed residues involved in transport. Interestingly, some of these residues correspond to those previously identified in other LeuT-fold transporters; however, we could also identify a novel relevant residue with such function. For the first time, by combined approaches of molecular docking and molecular dynamics simulations, we highlight the potential role of these residues in neutral amino acid transport. This novel information unravels new aspects of the human SLC6A14 structure–function relationship and may have important outcomes for cancer treatment through the design of novel inhibitors of SLC6A14-mediated transport.